The Intersection of Culture and Speaking Ability: Examining Cultural Barriers to Speaking Proficiency in Students - Andi Anugrah Surya Ardhy; Agus Fadilah Ajis (English Department FBS UNP, 2025)
This study explores the impact of cultural awareness, language learning environment, and cultural barriers on students' foreign language speaking ability. Involving 80 English language students at Universitas Muhammadiyah Muara Bungo, this study used a quantitative method by purposively selecting a sample of 56 students based on specific criteria, including English comprehension and cultural awareness. A Likert-scale questionnaire was used as the research instrument, distributed through Google Forms, and the results were analysed using descriptive statistics (SPSS). The results showed that cultural awareness is important in improving speaking ability, and students who better understand cultural values and norms communicate more effectively. A conducive learning environment, supported by social interaction and experiential teaching methods, strengthens students' speaking skills. However, cultural barriers such as anxiety about cultural mistakes and misunderstanding of communication norms remain challenges that must be overcome through cultural sensitivity training and inclusive learning. The uniqueness of this study lies in its multidisciplinary approach, which combines aspects of psychology, education, and cultural anthropology to understand the complex interactions between culture and students' speaking ability in the context of foreign language learning. Therefore, this research can potentially contribute to developing more effective and sustainable language learning strategies in the era of cross-cultural communication.